2011
DOI: 10.1017/s0021859611000177
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for determining rice critical nitrogen concentration

Abstract: SUMMARYA reliable evaluation of crop nutritional status is crucial for supporting fertilization aiming at maximizing qualitative and quantitative aspects of production and reducing the environmental impact of cropping systems. Most of the available simulation models evaluate crop nutritional status according to the nitrogen (N) dilution law, which derives critical N concentration as a function of above-ground biomass. An alternative approach, developed during a project carried out with students of the Cropping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Besides the scientific results, this study-performed with students of a cropping systems MS course and following previous experiences (e.g., Confalonieri et al, 2011a;Graves et al, 2002)-further demonstrated the key role of models in education (Van Dam et al, 1997).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Besides the scientific results, this study-performed with students of a cropping systems MS course and following previous experiences (e.g., Confalonieri et al, 2011a;Graves et al, 2002)-further demonstrated the key role of models in education (Van Dam et al, 1997).…”
Section: Discussionsupporting
confidence: 69%
“…The latter, following previous experiences (e.g., Confalonieri et al, 2011a), was the use of models as tools for supporting education. The former was analyzing and modeling the effect of floodwater level, N fertilization, and sowing density on the rate of rice plant elongation.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…So, it is sensible to confirm sufficient N accumulation prior to the onset of reproductive phase for grain filling and development. Furthermore, the algorithms obtained on the basis of this concept can be coupled with other generic crop growth and management models applicable to rice, such as RiceGrow and MAZINGA (Tang et al, 2009;Confalonieri et al, 2011). The existing models could get assistance from the newly established relationships on a large dataset to intensify the domain of the genotype x environment x management landscape, in which their yield prediction methods are effective.…”
Section: Application Of Nc Dilution Curve For In-season Yield Estimationmentioning
confidence: 99%
“…(1998) and Confalonieri et al . (2011). The Nmax, Nc and Nmin curves of plant and organs of rice was developed in the Yangtze River Reaches as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%